IMPACT OF SEXUAL COMMUNICATION ON MARITAL STABILITY OF COUPLES IN UKUM LOCAL GOVERNMENT AREA OF BENUE STATE: COUNSELLING INTERVENTION - Akume, Gabriel Terzungwe; Saatan, Ruth Movihinze (Sokoto Educational Review, 2013)
This study investigated the impact o f sexual communication on marital stability o f couples in Ukum local government area o f Benue State. The variable examined in this study was sexual communication on marital stability o f couples. A research question and hypothesis (at 0.5 level o f significance) each was formulated to guide the study. The survey research design was used with 384 respondents randomly selected from a population of 70,360 married couples in the study area. A self structured, Marital Communication and Stability Inventory (MCSI) was used as an instrument to collect data for the study. The data obtained was analysed using frequencies, percentages and Chi-square statistics. It was found that, sexual communication have significant impact on marital stability o f couples in the area o f study. Based on the finding, the study therefore recommends among others, that counsellors should start organising premarital counselling discussions as well as lectures, at adolescent stage of secondary school years, so as to catch the pupils young for the rudiments o f marital stability, so that when such children eventually get married, they will already be well equipped with the rudiments o f happy marital life and live a life o f peaceful co-existence.